Association between the reactivity of local cerebral oxygen saturation after hypo-to-hypercapnic tests and delirium after abdominal surgery in older adults: A prospective study - Song, Jie; Cheng, Chen; Sheng, Kui; Jiang, Ling-Ling; Li, Yun; Xia, Xiao-Qiong; Hu, Xian-Wen (Frontiers in Psychiatry, 2022)
Objective: This study aims to investigate the correlation between the changes in the regional cerebral oxygen saturation (rSO2) and postoperative delirium in older adults undergoing major abdominal surgery. Methods: This prospective study enrolled older adults scheduled for elective major abdominal surgery at the Second Affiliated Hospital of Anhui Medical University from August 2021 to January 2022. The change in rSO2 from baseline was determined using the hypo-to-hypercapnic test. The outcome was the occurrence of postoperative delirium. Results: Ultimately, 101 participants were included for analysis. Sixteen (15.8%) participants developed postoperative delirium. Compared with the non-delirium participants, the mean arterial pressure and heart rate were not significantly different in the postoperative delirium group at T0, T1, T2, T3, T4, and T6 (all P interaction > 0.05), but the delirium group showed lower pH, lower PaO2, and higher lactate levels at T4, T5, and T6 (all P interaction < 0.05). rSO2 was 69.0 (63.2–75.2), 70.7 ± 7.3, 68.2 ± 7.5, 72.1 ± 8.0, 69.9 ± 7.8, 67.4 ± 7.2, and 71.7 ± 8.1 at T0, T1, T2, T3, T4, and T6, respectively; the postoperative change of rSO2 during the hypercapnia test (TΔrSO2%) was 6.62 (5.31–9.36). The multivariable analysis showed that the Cumulative Illness Rating Scale (odd ratio, OR = 1.89, 95% confidence interval, CI: 1.10–3.25, P = 0.021), preoperative albumin levels (OR = 0.67, 95% CI: 0.48–0.94, P = 0.022), rSO2 at T4 (OR =0 .61, 95% CI: 0.41–0.89, P = 0.010), and postoperative TΔrSO2% (OR = 0.80, 95% CI: 0.66–0.98, P = 0.028) were independently associated with postoperative delirium in older adults undergoing elective abdominal surgery. Conclusion: The rSO2 measured at T4 and postoperative TΔrSO2% were independently associated with postoperative delirium in older adults undergoing elective abdominal surgery.